2016
DOI: 10.7314/apjcp.2016.17.3.1473
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Cigarette Smoking and Associated Factors among Male Citizens in Tehran, Iran

Abstract: Background: Cigarette smoking is as the leading cause of cancer mortality and other chronic diseases in males worldwide. The prevalence of cigarette smoking is different across and within countries by age, education level, occupation, and so on. This study aimed to determine the prevalence of cigarette smoking and its relationship with individuals' demographic factors and BMI in adolescent men living in Tehran, Iran. Materials and Methods: This study involved secondary analysis of the 'Urban Health Equity Asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 28 publications
2
2
2
Order By: Relevance
“…In other words, the young showed a stronger tendency to smoke (25,45,46). Contrary to the present study, some studies reported higher rates of TU at higher ages (4,47,48). This difference might be explained by different features of the target populations and the age ranges.…”
Section: Discussioncontrasting
confidence: 99%
“…In other words, the young showed a stronger tendency to smoke (25,45,46). Contrary to the present study, some studies reported higher rates of TU at higher ages (4,47,48). This difference might be explained by different features of the target populations and the age ranges.…”
Section: Discussioncontrasting
confidence: 99%
“…In other words, the young showed a stronger tendency to smoke [25,45,46]. Contrary to the present research, another study reported a higher rate of TU at a higher age [4,47,48]. This divergence might be explained by different features of the target populations and the age ranges.…”
Section: Discussioncontrasting
confidence: 99%
“…The prevalence of tobacco use was higher among those above 30 compared to those below 30. Consistent with this finding, other studies reported the increasing rate of tobacco use with higher age (4,30,31). Contrarily, some other works indicated a higher tendency to tobacco use among youngsters (13,32,33).…”
Section: Discussionsupporting
confidence: 80%